2016
DOI: 10.3102/0034654315584955
|View full text |Cite
|
Sign up to set email alerts
|

Do First-Year Seminars Improve College Grades and Retention? A Quantitative Review of Their Overall Effectiveness and an Examination of Moderators of Effectiveness

Abstract: We review the effectiveness of first-year seminars based on the widely used criteria of first-year grades and the 1-year retention rate. Meta-analytic results indicate that first-year seminars have a small average effect on both first-year grades (k = 89, N = 52,406, δ = 0.02) and the 1-year retention rate (k = 195, N = 169,666, δ = 0.11). We discuss the implications of these small effects and show that they are meaningful and have important consequences. Results also indicate that the effectiveness of first-y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 62 publications
5
61
0
2
Order By: Relevance
“…By including both assessment of student learning, and long-term data analysis, our implementation process supported previous research that indicates one of the roles of orientation is increasing awareness of the self as a learner, establishing social support networks, and increasing retention (Boening & Miller, 2005;Hunter, 2006;Jamelske, 2009;Mayhew et al, 2010;Permzadian & Credé, 2016). The significant assessment process built into the program also helped create a convincing case for dedicating increased resources to the program.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…By including both assessment of student learning, and long-term data analysis, our implementation process supported previous research that indicates one of the roles of orientation is increasing awareness of the self as a learner, establishing social support networks, and increasing retention (Boening & Miller, 2005;Hunter, 2006;Jamelske, 2009;Mayhew et al, 2010;Permzadian & Credé, 2016). The significant assessment process built into the program also helped create a convincing case for dedicating increased resources to the program.…”
Section: Discussionsupporting
confidence: 52%
“…In addition, community colleges struggle to reach first year retention rates of fifty percent (Derby & Smith, 2004;Hollins, 2009;Permzadian & Credé, 2016). Community colleges have often failed to make the connection between orientation, and student retention, success, and graduation (Derby & Smith, 2004;Martin et al, 2014;Permzadian & Credé, 2016). Rather than viewing orientation as the opportunity to set students on the path to success, and impact student completion outcomes, community colleges are too often concerned that requiring participation in orientation presents an enrollment barrier for students.…”
Section: Orientationmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, many FCS institutions had student life skills (SLS) courses required for DE students, but since implementing SB 1720, some colleges have eliminated the requirement. Although Permzadian and Credé (2015) found only small effect sizes on increasing first-year GPAs and first-year retention rates for similar courses, they provided recommendations for improving the courses' success. Courses should include all students, not merely those with limited academic preparedness; have faculty, as compared to undergraduate or graduate students, instruct the courses; and focus on orienting the students to college by providing the relevant college knowledge that Conley (2008) recommends.…”
Section: Recommendations For Institutional Practicementioning
confidence: 99%
“…Of course the instructors must also use interactive exercises and adult learning styles if boredom is to be reduced. The moves on a broader front to build first year seminars that prepare students for engaging in university studies (see Permzadian & Crede, 2015) may also assist. But our study confirmed for the current 2012-2015 psychology students in our Australian sample that class attendance in tutorials relates significantly to subject performance just as attendance at associated labs had for economics students (Adair & Swinton, 2012).…”
Section: Limitations Summary and Future Researchmentioning
confidence: 99%